THE ROLE OF THE FAMILY IN BUILDING MORAL AND MORAL IMMUNITY AGAINST INFORMATION ATTACKS IN CHILDREN'S UPbringing (Universal International Scientific Journal, 2026)
This article discusses the issues of protecting young people from various ideological threats and information attacks in the context of globalization and an information society. In particular, the role of family psychology in raising children and its importance in forming spiritual and moral immunity are analyzed. The concept of gender stereotypes and their impact on child upbringing and the formation of social consciousness are also scientifically examined. It is argued that the formation of healthy psychological relationships, national values, and principles of equality in the family environment is an important factor in the development of young people into well-rounded individuals.
Keywords: family psychology; information attacks; moral and ethical immunity